2014
DOI: 10.1371/journal.pone.0078583
|View full text |Cite|
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 and Cystic Fibrosis Lung Disease: A Systematic Meta-Analysis

Abstract: BackgroundTo systematically assess the literature published on the clinical impact of Influenza A(H1N1)pdm09 on cystic fibrosis (CF) patients.MethodsAn online search in PUBMED database was conducted. Original articles on CF patients with Influenza A(H1N1)pdm09 infection were included. We analyzed incidence, symptoms, clinical course and treatment.ResultsFour surveys with a total of 202 CF patients infected by Influenza A(H1N1)pdm09 were included. The meta-analysis showed that hospitalisation rates were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
1
28
0
1
Order By: Relevance
“…These results are especially compelling because CFTR had independently been shown to inhibit IL-8 production in response to inflammatory mediators. This is consistent with a recent study demonstrating that CFTR heterozygous (wild-type/⌬f508) mice are less susceptible to influenza injury than their homozygous wild-type mice although patients with cystic fibrosis are more susceptible to infections with influenza virus (87). Robust early inflammatory responses normally observed in wild-type animals early in infection are dampened in CFTR heterozygote mice, whereas the cytokine profile was altered later in infection (1,110).…”
Section: Role Of Ion Transport In Influenza Pathologysupporting
confidence: 91%
See 1 more Smart Citation
“…These results are especially compelling because CFTR had independently been shown to inhibit IL-8 production in response to inflammatory mediators. This is consistent with a recent study demonstrating that CFTR heterozygous (wild-type/⌬f508) mice are less susceptible to influenza injury than their homozygous wild-type mice although patients with cystic fibrosis are more susceptible to infections with influenza virus (87). Robust early inflammatory responses normally observed in wild-type animals early in infection are dampened in CFTR heterozygote mice, whereas the cytokine profile was altered later in infection (1,110).…”
Section: Role Of Ion Transport In Influenza Pathologysupporting
confidence: 91%
“…Quantitative studies in cystic fibrosis airways demonstrated that the center of infection is localized in the mucous gel layer, with virtually no bacteria detected adherent to, or within, epithelial cells (86). Treatments resulting in hypersecretion of mucin in animal models did not show significantly enhanced airway obstruction, or increased during infections, indicating that mucin per se was not responsible for these effects (87). In contrast, decreasing the ASL volume through overexpression of the ␤-ENaC led to reduced mucociliary transport, increased neutrophilic inflammation, poor bacterial clearance, and enhanced airway obstruction (86).…”
Section: Role Of Ion Transport In Influenza Pathologymentioning
confidence: 99%
“…The significance of our studies is underscored by ample evidence signifying that CFTR is involved in the regulation of immune responses against influenza infection. First, meta‐analysis found that the 2009 H1N1 pandemic influenza virus infection caused greater morbidity and mortality in patients with cystic fibrosis in comparison with patients with asthma and patients without other underlying respiratory conditions (15). Second, genetic analysis of primary cystic fibrosis and normal airway epithelium following influenza infection found that more genes were altered (both activated and inhibited) in normal respiratory epithelial cells than in cystic fibrosis cells.…”
Section: Discussionmentioning
confidence: 99%
“…The current management consists of the seasonal influenza vaccination and passive immunoprophylaxis against respiratory syncytial virus infection, which is recommended in certain countries [5]. Specific antiviral treatments against influenza are available as therapeutic strategies and prescribed to CF patients [6]. However, there are no available treatments against RV infections.…”
Section: Introductionmentioning
confidence: 99%